(untitled) (Bangladesh Journal of Nuclear Agriculture, 2023)
The soil samples collected from an agricultural region near the Sungai Chalit mine site in Raub, Pahang, Malaysia were subjected to X-ray powder diffraction (XRPD) analysis for the first time. The PanAnalytikX’pert Pro XRD equipment at the XRD laboratory, Material Technology, Nuclear Malaysia, was used to identify the clay minerals present in the samples. After thorough analysis of all samples, it has been determined that microcline is found in every sample, whereas bytownite has been detected in just three unique samples (DS2, DS15, and DS17). Two discrete variants of zeolite were discerned in two specimens, denoted as DS2 and DS17. Sample DS6 contains kaolinite. Sample C13 comprises four clay minerals: microcline, anorthite, birnessite, and tremolite. The occurrence of microcline in soil signifies the erosion of rocks abundant in feldspar, such as granite, resulting in a reduction of essential minerals like potassium and calcium. This depletion has the potential to affect plant nutrition and crop yield. Bangladesh J. Nuclear Agric, 37(2): 121-133, 2023